2007
DOI: 10.1007/s00442-006-0594-x
|View full text |Cite
|
Sign up to set email alerts
|

Convergence patterns and multiple species interactions in a designed plant mixture of five species

Abstract: It is known that convergence and divergence can occur in complex plant communities, but the relative importance of biotic and abiotic factors driving these processes is less clear. We addressed this issue in an experiment using a range of mixed stands of five species that are common in Swiss fens (Carex elata, C. flava, Lycopus europaeus, Lysimachia vulgaris and Mentha aquatica) and two levels of water and nutrients. One hundred and seventy-six experimental mixtures were maintained in large pots (75 l) for two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…legumes) in the resident community. However, invasion success was most strongly dependent on the biological difference between the invader and the invaded community (Strauss et al 2006, Suter et al 2007, permitting species that belonged to a functional group absent from a community to invade more easily than species belonging to a functional group already present (Fargione et al 2003, Turnbull et al 2005b). This strong negative interaction between residents and invaders of the same functional group could be due to overlapping resource requirements (e.g.…”
Section: Invasibility and Invasivenessmentioning
confidence: 99%
“…legumes) in the resident community. However, invasion success was most strongly dependent on the biological difference between the invader and the invaded community (Strauss et al 2006, Suter et al 2007, permitting species that belonged to a functional group absent from a community to invade more easily than species belonging to a functional group already present (Fargione et al 2003, Turnbull et al 2005b). This strong negative interaction between residents and invaders of the same functional group could be due to overlapping resource requirements (e.g.…”
Section: Invasibility and Invasivenessmentioning
confidence: 99%
“…The stronger intra-than inter-specific competition has been reported by many other studies (e.g. Suter et al, 2007;Johansson & Keddy, 1991). However Huckle et al, (2002) found the reverse pattern while (Aguiar et al, 2001) found equal strength of intra-and inter-specific competition.…”
Section: Change In Species Final Biomass Proportional Abundancesmentioning
confidence: 43%
“…According to Connolly & Wayne (2005), the large differences in RGR (species identity) observed in our experiment, would by themselves lead to considerable change in species' relative abundance in mixture, as they are much the strongest element in modifying structure. The importance of species identity relative to intraand inter-specific competition in structuring community final biomass has also been reported in other studies (Connolly & Wayne, 2005;Ramseier et al, 2005;Suter et al, 2007).…”
Section: Determinant Of Change In Species Biomass Compositionmentioning
confidence: 69%
“…The net relative growth rate (RGR) between planting and harvesting was calculated following Connolly and Wayne (1996) and Suter et al (2007). For the calculation of RGR, the biomass of the three individuals per species and pot were pooled.…”
Section: Discussionmentioning
confidence: 99%